PERAN GURU DALAM MENCIPTAKAN LINGKUNGAN BELAJAR YANG NYAMAN DAN KOMUNIKATIF UNTUK MENINGKATKAN KEAKTIFAN SISWA DI KELAS - Nadia Oktaviani; Nor Azizah Inti Kolbi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
This study aims to describe the teacher’s role in creating a comfortable and communicative learning environment to improve students’ activeness in the classroom. This research used a qualitative approach with a case study design conducted at SDN 04 Koto Baru. This research used a qualitative approach with a descriptive case study design conducted at SDN 04 Koto Baru. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that teachers have an important role in creating a conducive learning atmosphere through good communication, the use of group learning methods, providing motivation, and building harmonious relationships between teachers and students. A comfortable and communicative learning environment can increase student participation in discussions, courage in expressing opinions, and cooperation among students in the classroom. In addition, teachers also act as mediators in resolving conflicts among students so that a safe and enjoyable learning atmosphere is created. Therefore, the teacher’s role greatly influences the creation of a learning environment that supports increasing student activeness in the learning process. Keywords: teacher’s role, learning environment, communication, student activeness